The Influence of Organizational Culture and Work Discipline on Employee Performance - Yulian Rinawaty Taaha (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2021)
This study discusses the influence of organizational culture and work discipline on the performance of employees of PT. Megahputra Sejahtera Suzuki Pettarani Makassar. This research approach uses quantitative research. The data used in this study are primary data obtained from questionnaires. The sample of this research is the employees of PT. Megahputra Sejahtera Suzuki Pettarani Makassar, totaling 52 people. Data collection was carried out using a questionnaire. Data analysis used validity test, reliability test, classical assumption test, multiple linear regression analysis. Partial test, simultaneous test, and determination test. The results of the study found that organizational culture has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Simultaneously organizational culture and work discipline have a positive and significant influence on employee performance at PT. Megahputra Sejahtera Suzuki Pettarani Makassar.